Correction Of Grammatical Mistakes In Classroom Interaction - Asti Ramadhani E Lestari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
This study aims at describing the grammatical mistakes at the first year classes of English Department of State University of Jakarta and to investigate the correction of those grammatical mistakes. This study used a case study as a method. It used non-participant observation as the instrument of the study. There are six classes were being observed more than five times, total of the data sources is 39 classroom activities. The result of this study shows that students at the first year classes of ED UNJ made grammatical mistakes mostly in number while the students did not make mistakes in definiteness. It also shows that most teachers are aware to students’ grammatical mistakes since more than 50% of the mistakes were corrected by the teacher. The result of this study shows that the most effective correction of grammatical mistakes is clarification request.Key words: Grammatical Mistakes, Correction of Grammatical Mistakes, Classroom Interaction